195k views
14 votes
If there is a solution I must put it down please help.

If there is a solution I must put it down please help.-example-1
User The Alpha
by
5.5k points

1 Answer

2 votes

Explanation:

a). x-5 = -4

⇛x = -5+5

Therefore, x = 0 = 1

b). -8x - 2 = -8

⇛-8x = -8-2

⇛-8x = -10

⇛x = -10÷-8

⇛x = 10/8

Therefore, x = 5/4

c). 3x + 26 = 5x

⇛3x -5x = -26

⇛-2x = -26

⇛x = -26÷-2

⇛x = -26/-3

Therefore, x = 26/3

d). 12 = 4(-17+ 5x)

⇛12 = -68 + 20x

⇛12 +68 = 20x

⇛80 = 20x

⇛x = 20/80

Therefore, x = 1/4

e). x = (3/4)x -2

⇛ x -(3/4)x = -2

Therefore, x = 6

f). 0.5x + 4.75 = 13

⇛0.5x = 13-4.75

⇛0.5x = 8.25

⇛x = 8.25/0.5

Therefore, x = 16.5

g). 127.5 = 12x+(60/8)

⇛127.5 = 12x + (30/4)

⇛-12x = (30/4) - 127.5

⇛-12x = (30/4) - (127.5/1)

⇛-12x = (30*1 - 127.5*4)/4

⇛-12x = (30- 510)/4

⇛-12x = -480/4

⇛-12x = -240/2

⇛-12x = -120

⇛x = -120/-12

Therefore, x = 10

h). (1/7)(-20-4x)=-4

⇛(-20-4x)/7 = -4/1

⇛1(20-4x) =7 (-4)

⇛20 - 4x = -28

⇛-4x = -28-20

⇛-4x = -8

⇛x = -8/-4

Therefore, x = 2

i). -18 = x - 12

⇛-18 + 12 = x

⇛-6 = x

Therefore, x = -6

j). -7(2/3) = 4x-9

⇛-(21+2)/3 = 4x - 9

⇛-(23/3) = 4x -9

⇛-(23/3) + 9 = 4x

⇛-(23/3) + (9/1) = 4x

⇛-(23*1 + 9*3)/3 = 4x

⇛(-23 + 27)/3

⇛(4/3) = 4x

⇛(4/3)÷4 = x

⇛(4/3) × (1/4) = x

⇛(4*1)/(3*4) = x

⇛4/12 = x

Therefore, x = 4/12

l). -6(2.5x + 8) = -123

⇛-15x -48 = -123

⇛-15x = -123+ 48

⇛-15x = -75

⇛x = -75/-15

Therefore, x = 5

m). -19x = 100 + x

⇛-19x - x = 100

⇛-20x = 100

⇛x = 100/-20

Therefore, x = -5

n). 0.2x - 0.5 = 1.2

⇛0.2x = 1.2 + 0.5

⇛0.2x = 1.8

⇛x = 1.8/0.2

Therefore, x = 4

o). (-2)² - 3x = -17

⇛(-2*-2) - 3x = -17

⇛4 - 3x = -17

⇛-3x = -17-4

⇛-3x = -21

⇛x = -21/-3

Therefore, x = 7

p). -(1/2)x -(4/5) = 19/4

⇛-(1/2)x = (19/4) + (4/5)

Take the LCM of the denominator 4 and 5 is 20.

⇛-(1/2)x = (19*5 + 5*4)/20

⇛-(1/2)x = (95 + 16)/20

⇛-(1/2)x =111/20

⇛x = (111/20) + (1/2)

Again take the LCM of the denominator 20 and 2 is 20.

⇛x = (111*1 + 1*10)/20

⇛x = (111 + 10)/20

⇛x = (121/20)

Therefore, x = 121/20

q). (x/8) + 2 = 1/4{(5/16) + 8}

⇛(x/8) + 2 = (5/64) + 2

⇛(x/8) + 2 = (5/64) + (2/1)

Take the LCM of the denominator 1 and 64 is 64 in RHS.

⇛(x/8) +2 = (5*1 + 2*64)/64

⇛(x/8) + 2 = (5 + 128)/64

⇛(x/8) + 2 = 133/64

⇛x/8 = (133/64) - 2

⇛x/8 = (133/64) - (2/1)

Take the LCM of the denominator 1 and 64 is 64 in RHS.

⇛x/8 = (133*1 - 2*64)/64

⇛x/8 = (133 - 128)/64

⇛x/8 = 5/64

On applying cross multiplication, then

⇛x(64) = 8(5)

⇛64x = 40

⇛x = 40/64

⇛x = (40÷4)/(64÷4)

⇛x = 10/12

⇛x = (10÷2)/(16÷2)

Therefore, x = 5/8

r). -6 = -3{(1/7)x + (4/14)}

⇛-6 = -(3/7)x -(6/7)

⇛-6 + (6/7) = -(3/7)x

⇛-(6/1) + (6/7) = -(3/7)x

Take the LCM of the denominator 1 and 7 is 7 in LHS.

⇛(-6*7 + 6*1)/7 = -(3/7)x

⇛(-42 + 6)/7 = -(3/7)x

⇛-(36/7) = -(3/7)x

On applying cross multiplication, then

⇛7(36) = 21x

⇛252 = 21x

⇛252/21= x

⇛12 = x

Therefore, x = 12

s). (1/4)x = 11/4

⇛x = (11/4) - (1/4)

⇛x = (11-1)/4

⇛x = 10/4

⇛(10÷2)/(4÷2)

Therefore, x = 5/2

t). x - (-3) = 9

⇛x + 3 = 9

⇛x = 9-3

Therefore, x = 6.

Please let me know if you have any other questions.

User Bouvierr
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.